Laminectomy with instrumented fusion vs. laminoplasty in the surgical treatment of cervical ossification of the posterior longitudinal ligament: A multicenter retrospective study. (December 2021) - Lee, Jong Joo; Kim, Hyung Cheol; Jeon, Hyeong Seok; An, Seong Bae; Kim, Tae Woo; Shin, Dong Ah; Yi, Seong; Kim, Keung Nyun; Yoon, Do Heum; Shin, Hyun Chul; Nagoshi, Narihito; Watanabe, Kota; et al.
Highlights: Both LF and LP demonstrated improvement in neurologic outcome for patients with multilevel cervical OPLL. There was no difference in reoperation rate between the two surgical methods. Complication rates including C5 palsy were higher in LF patients than LP patients. Abstract: Laminectomy with instrumented fusion (LF) has demonstrated better prevention of ossification of posterior longitudinal ligament (OPLL) growth compared to laminoplasty (LP). There remains uncertainty, however, as to which surgical approach is more beneficial with respect to clinical outcomes and complications. We retrospectively reviewed 273 cervical OPLL patients of more than 3 levels, from the two institutions' databases, who underwent LF or LP between January 1998 and January 2016. Each 273 patient (85 with LF, 188 with LP) was assessed for postoperative neurologic and radiologic outcomes, complications and reoperations. The mean length of follow-up was 40.11 months. There were baseline differences between cohorts. Overall, postoperative JOA recovery rate at last follow up was significantly better in the LP group with similar improvement in visual analog neck score. Postoperative C2-7 Cobb angle was decreased compared to baseline for both LF and LP cohorts, but there was no significant difference between groups. Complications occurred in 19 (22.35%) LF patients, and 11 (5.85%) LP patients, with higher incidence of C5 palsy and instrumentation failure in the LF group. Four LF patients (4.71%) and five LP patients (2.66%) underwent reoperation during the follow up period.